Expression of polycomb protein BMI‐1 maintains the plasticity of basal bronchial epithelial cells. Issue 16 (24th August 2016) - Torr, Elizabeth; Heath, Meg; Mee, Maureen; Shaw, Dominick; Sharp, Tyson V.; Sayers, Ian
Abstract: The airway epithelium is altered in respiratory disease and is thought to contribute to disease etiology. A caveat to disease research is that the technique of isolation of bronchial epithelial cells from patients is invasive and cells have a limited lifespan. The aim of this study was to extensively characterize the plasticity of primary human bronchial epithelial cells that have been engineered to delay cell senescence including the ability of these cells to differentiate. Cells were engineered to express BMI‐1 or hTERT using viral vector systems. Cells were characterized at passage (p) early (p5), mid (p10), and late (p15) stage for: BMI‐1, p16, and CK14 protein expression, viability and the ability to differentiate at air–liquid interface (ALI), using a range of techniques including immunohistochemistry (IHC), immunofluorescence (IF), transepithelial electrical resistance (TEER), scanning electron microscopy (SEM), MUC5AC and beta tubulin (BTUB) staining. BMI‐1‐expressing cells maintained elevated levels of the BMI‐1 protein and the epithelial marker CK14 and showed a suppression of p16. BMI‐1‐expressing cells had a viability advantage, differentiated at ALI, and had a normal karyotype. In contrast, hTERT‐expressing cells had a reduced viability, showed limited differentiation, and had an abnormal karyotype. We therefore provide extensive characterization of the plasticity of BMI‐1 expressing cells in the context of the ALI model. These cells retain properties of wild‐type cells and may be useful to characterize respiratory disease mechanisms in vitro over sustained periods. Abstract : The airway epithelium is altered in respiratory disease however the isolation of bronchial epithelial cells from patients for study is invasive and cells have a limited lifespan. We have developed an approach to delay cell senescence and provide extensive characterisation of the plasticity of these engineered cells including the ability of cells to differentiate. These cells retain properties of wild‐type cells and may be useful to characterise respiratory disease mechanisms in vitro over sustained periods.